An Evidence-Based Review of Fat Modifying Supplemental Weight Loss Products - Amy M. Egras; William R. Hamilton; Thomas L. Lenz; Michael S. Monaghan (Journal of Obesity)
Objective. To review the literature on fat modifying dietary supplements commonly used for weight loss. Methods. Recently published randomized, placebo-controlled trials were identified in PubMed, MEDLINE, International Pharmaceutical Abstracts, Cochrane Database, and Google Scholar using the search terms dietary supplement, herbal, weight loss, obesity, and individual supplement names. Discussion. Data for conjugated linoleic acid (CLA), Garcinia cambogia, chitosan, pyruvate, Irvingia gabonensis, and chia seed for weight loss were identified. CLA, chitosan, pyruvate, and Irvingia gabonensis appeared to be effective in weight loss via fat modifying mechanisms. However, the data on the use of these products is limited. Conclusion. Many obese people use dietary supplements for weight loss. To date, there is little clinical evidence to support their use. More data is necessary to determine the efficacy and safety of these supplements. Healthcare providers should assist patients in weighing the risks and benefits of dietary supplement use for weight loss.